Literature Review: Pengaruh Defisiensi Vitamin D terhadap Proses Pertumbuhan Tulang pada Balita Stunting - Fathia Salsabila Fakhira; Herry Garna; Dyana Eka Hadiati (UNISBA Press, 2023)
Abstract. Stunting is one of the problems of linear growth failure due to unbalanced intake of macronutrients and micronutrients. One of the micronutrients that has a close relationship with the incidence of stunting is vitamin D which plays an important role in the development and maintenance of bone mineralization and helps the process of bone formation. Descriptive analitics research method through literature study by collecting several previous studies with the purpose to determine the effect of vitamin D deficiency on the process of bone growth in stunting toddlers. The results of this study show that there is an effect of vitamin D deficiency on the process of bone growth in stunted toddlers by inhibiting the function of IGF-1 in increasing osteoblastogenesis thereby reducing the rate of bone growth. In conclusion, vitamin D has an important role in the process of bone growth in stunting toddlers. Keywords: Bone; stunting; toddler; vitamin D Abstrak. Stunting merupakan salah satu permasalahan kegagalan pertumbuhan linear akibat asupan gizi makronutrien dan mikronutrien yang tidak seimbang. Salah satu zat mikronutrien yang memiliki hubungan erat dengan kejadian stunting adalah vitamin D yang berperan penting dalam pengembangan dan pemeliharaan mineralisasi tulang serta membantu proses formasi tulang. Metode penelitian analisis deskriptif melalui studi literatur dengan mengumpulkan beberapa penelitian terdahulu dengan tujuan untuk mengetahui pengaruh defisiensi vitamin D terhadap proses pertumbuhan tulang pada balita stunting. Hasil studi ini menunjukan adanya pengaruh defisiensi vitamin D terhadap proses pertumbuhan tulang pada balita stunting yaitu terhambatnya fungsi IGF-1 dalam peningkatan osteoblastogenesis sehingga menurunkan laju pertumbuhan tulang. Kesimpulan vitamin D memiliki peranan penting terhadap proses pertumbuhan tulang pada balita stunting. Kata Kunci: Balita; stunting; tulang; vitamin D